Aphallia: Report of three cases and literature review - Davood Nasiry Zarrin Ghabaee; Davood Nasiry Zarrin Ghabaee; Ramezan Ali Naeimi; Seyed Javad Seyedi; Seyed Abdollah Mousavi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Aphallia or penile agenesis is a rare malformation accompanying with no phallus. This anomaly is extremely rare with abnormality of urogenital system and psychological consequences. Its outbreak is estimated 1 out of 10-30 million births. Case: Reviewing 3 cases of male external genitalia agenesis, which associated with multiple anomalies of musculoskeletal, cardiovascular and genitourinary system. Conclusion: Aphallia has psychosocial consequences and a guarded prognosis. This study showed that if the kidney failure is due to its obstruction, these patients will be born in more favorable conditions and the future treatment measures will be directed to keep the external genitalia (male) through timely diagnosis and prenatal surgery and timely bladder drainage